DECOMPENSATED URINARY BLADDER DUE TO BENIGN PROSTATIC HYPERPLASIA (LITERATURE REVIEW) - O.O. Sherstyuk; Y.V. Sarychev; S.M. Suprunenko; S.A. Sukhomlin; G.L. Pustovoit (Проблеми екології та медицини)
We conducted an analytical review of the literature on the problem of bladder decompensation in patients with benign prostatic hyperplasia. Benign prostatic hyperplasia is one of the most common diseases in aging men. As is known, with the development of benign prostatic hyperplasia due to infravesicular obstruction, the resistance to urine flow increases. As a result of a prolonged overload, the bladder is restructured, and it goes through three successive stages: compensation, subcompensation, and decompensation. Irreversible changes develop in the epithelial, muscular, and nerve tissues of the bladder. With benign prostatic hyperplasia due to intravesical hypertension, persistent microcirculation disorders occur in the walls of the bladder, which leads to the appearance of chronic detrusor ischemia, and can be a predictor of its fibrotic changes and decompensation. There is a correlation between the pathology of the vascular system and the development of symptoms of the lower urinary tract against the background of benign prostatic hyperplasia. Improvement of lower urinary tract perfusion can be considered a therapeutic strategy for the treatment of bladder dysfunction.